Physical exam skills - Alfredo Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
The world has changed, we live quickly in a vertiginous whirlwind and the way of practicing medicine also has changed. In the field of medical care there is currently a not favorable universal trend. It is very close to the professors of the clinical area, the minimization of the patient´s physical examination value, even its obviation in many cases -resulting from trusting too much in a shallow interview and, especially, in the modern complementary diagnostic means to conduct the medical act and for decision making in each case.